REGULASI PRODUK FARMASI DAN SUPLEMEN KESEHATAN BERBASIS HERBAL: TINJAUAN PUSTAKA TERHADAP PERAN BPOM DAN PERLINDUNGAN KONSUMEN - Gunawan Widjaja (Jurnal Kesehatan, 2026)
Herbal-based pharmaceutical products and health supplements are increasingly in demand amongst the public as they are considered more natural and safer. However, the rise in the consumption of herbal products is also accompanied by various risks, such as the circulation of illegal products, exaggerated claims of benefits, incorrect labelling, and the potential presence of pharmaceutical chemicals. This article aims to review the regulation of herbal-based pharmaceutical products and health supplements in Indonesia, focusing on the role of the Indonesian Food and Drug Authority (BPOM) and consumer protection. The method employed was a literature review, examining scientific literature, legislation, and official sources relating to the supervision of herbal products. The results of the review indicate that the BPOM plays a central role in pre-market and post-market supervision, including registration, labelling, distribution oversight, and enforcement against products that breach regulations. On the other hand, consumer protection requires legal certainty, accurate information and guarantees of product safety for the public. Consequently, strengthening regulation, supervision and consumer education are crucial steps towards ensuring the safe, high-quality and responsible use of herbal products.